2012
DOI: 10.1016/j.joep.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic identity and discrimination among children

Abstract: We engaged over 430 Canadian children in a series of activities designed to reveal their evaluations of three ethnic groups (White, East Asian and South Asian), their identification with these groups, and their behavior towards them in a dictator game. Our experiments took place at the children's schools during their normal school day, allowing us to evaluate the salience and effects of ethnic identities on economically relevant behavior in an important natural setting. We find that children from the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…The results of the present study demonstrate that kith-and-kin rationality may appear early in preschool years, as they donated more stickers to friends than to strangers. However, this result contradicted with another study which found that 5-8-year-old East Asian children in Canada seemed to show outgroup favoritism [ 29 ]. Here we should note that those children were Minority in Canada, and being prosocial to out-groups might help them adapt to local society.…”
Section: Discussioncontrasting
confidence: 68%
“…The results of the present study demonstrate that kith-and-kin rationality may appear early in preschool years, as they donated more stickers to friends than to strangers. However, this result contradicted with another study which found that 5-8-year-old East Asian children in Canada seemed to show outgroup favoritism [ 29 ]. Here we should note that those children were Minority in Canada, and being prosocial to out-groups might help them adapt to local society.…”
Section: Discussioncontrasting
confidence: 68%
“…These results join a small literature using dictator games to investigate discrimination among children. Related work shows Canadian white children tend to favor white children in the dictator game relative to minority recipients (Friesen et al, 2012)…”
Section: Resultsmentioning
confidence: 99%
“….813, p = .004). While it is unclear what baseline behavior to expect for this age group in Italy due to a lack of previous studies in such a setting, the results suggest that in low-Mafia high schools students show some out-group favoritism, possibly due to status consideration (Friesen et al, 2012) or dislike of their own group (Bilewicz and Kofta, 2011). Table 6 presents regressions that tests the robustness of the results in Figure 2 to adding control variables and standard error clustering at the class level.…”
Section: In-group Favoritismmentioning
confidence: 96%